Effect of Chemotherapy on hs- C Reactive Protein, Some Blood Picture and Kidney Function in Patients With Neuroblastoma - yaqoob, sama; Alsaadi, Jamal (University of Thi-Qar Journal of Science, 2023)
Background: Neuroblastoma, the most common extra-cranial malignant pediatric solid tumor and one with a high mortality rate. Children suffering from Neuroblastoma after chemotherapy suffer from anemia, severe infections, and effects on some organs of the body. Therefore, the current study aims to study the effect of chemotherapy on inflammatory factor (high-sensitivity C-reactive Protein), some hematological parameters such as white blood cells, platelets, and hemoglobin, and some kidney function such as urea and Creatinine in children with Neuroblastoma before and after three cycles of chemotherapy. Materials and methods:  70 cases were divided into three groups: Group A;  35 healthy children are included as a control group., and  group B; consists of 35 newly diagnosed patients   and  group C; following three chemotherapy rounds (same patients newly diagnosed), with an age range from 2 months to 12 years. They had attended Basrah Specialist Hospital for Children from May 2022 to the end of March 2023. Results: When compared to the control group, the results of the current study showed a significant rise (p˂0.05) in the levels of high-sensitivity C-reactive protein, white blood cells, and platelets in the sera samples of patients with NeuroblastomaConclusion: This study came to the conclusion that Neuroblastoma treatment considerably changed a number of hematological markers and hs-crp. Consequently, it is essential to monitor these signs.